Distribuição espaço-temporal e dinâmica populacional do Siri Callinectes Danae Smith, 1869 (Decapoda: Portunidae) na região adjacente à Baía de Babitonga, Santa Catarina - Sabino, Filipe Nathan Assunção [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Studies on the distribution of marine organisms are essential for obtaining information on regions affected by human activities and for the understanding of the population dynamics of species. Thus, the present study aimed to investigate the abundance, spatial-temporal distribution and population dynamics of the crab Callinectes danae in adjacent region of the Babitonga Bay. Biological and abiotic samples were obtained monthly in the region from July/2010 until June/2011. Samples were collected at 5, 8, 11, 14 and 17m deep, using a fishing boat equipped with doble -rig nets. The number of individuals and the following abiotic factors were recorded at each depth: salinity and bottom temperature, organic matter and sediment texture. A total of 3,999 individuals were collected, with difference between the numbers of males (229) and females (3770). The individuals were measured concerning the carapace width (CW) and classified according to the development stage. The estimated value where 50 % of individuals were able to reproduce was 75.2 mm (CW) for males and 62.9 mm (CW) for females. The value of L ∞ for the growth analysis was fixed based on literature values, where males and females showed the asymptotic width of 102.01 and 84.41 respectively, the growth constants of 0.007 and 0.006/day, as well as the longevity of 633 and 702 days. Prevalence of female in larger size classes may be associated with characteristics of this species, which individuals migrate to different regions depending on the life stage. Reproductive females search for areas with higher salinity, while juvenile and males preferably live in estuarine areas, corroborating with is found in the current literature. Reproduction was continuous showing that the sampled area has a primordial importance for the perpetuation of this species, since it shelters a very high percentage of reproductive females. The information from this study...

Estudos sobre a distribuição de organismos marinhos são essenciais para obtenção de informações sobre regiões afetadas por atividades antrópicas e para o entendimento da dinâmica populacional das espécies. Assim, o presente estudo visou investigar a abundância, a distribuição espaço-temporal e a biologia populacional do siri Callinectes danae na região adjacente à baía da Babitonga. O material biológico e abiótico foram obtidos mensalmente na região, no período de julho/2010 a junho/2011. As coletas foram efetuadas nas profundidades 5, 8, 11, 14 e 17m, com um barco de pesca com redes tipo double-rig. Em cada profundidade foram verificados o número de indivíduos e os parâmetros de salinidade e temperatura de fundo, matéria orgânica e textura do sedimento. Um total de 3.999 indivíduos foi coletado, com diferença entre o número de machos (229) e fêmeas (3770). Os indivíduos foram mensurados na largura de carapaça (LC), bem como classificados quanto ao estágio de desenvolvimento. O valor estimado onde 50% dos indivíduos estão aptos à reprodução foi de 75,2 mm (LC) para os machos e 62,9 mm (LC) para as fêmeas. Para a análise do crescimento foi fixado o valor de L∞ com base nos valores da literatura, sendo que os machos e fêmeas apresentaram respectivamente a largura assintótica de 102,01 e 84,41, as contantes de crescimento de 0,007 e 0,006/dia, bem como a longevidade de 633 e 702 dias. A predominância de fêmeas nas maiores classes de tamanho pode estar associada a características da espécie, cujos indivíduos migram para diferentes regiões conforme o estágio de vida. Fêmeas reprodutivas buscam áreas com maior salinidade enquanto juvenis e machos preferencialmente vivem em áreas estuarinas, corroborando ao encontrado na bibliografia. A reprodução foi contínua, portanto a área de coleta demonstra ser de suma importância para a perpetuação...
Keywords: Biologia - População; Siri; Siri azul; Decapode (Crustaceo); Decapoda (Crustacea)